Current software opportunities for generating routine EEG reports - A. A. Ivanov (Эпилепсия и пароксизмальные состояния)
Currently, recommendations for conducting routine EEG examinations have been developed, but the pattern on assessing and describing brain bioelectrical activity remains controversial. There is no single commonly accepted consensus approach to writing reports based on routine EEG data. This leads to the situation when each specialist describes EEG activity as he considers correct. The reports on EEG examinations vary greatly from clinic to clinic, from specialist to specialist, so they are often difficult to interpret. This article proposes a simple step-by-step scheme for assessing and describing brain bioelectrical activity recorded during a routine EEG examination, as well as a review of potential for current software to be applied for automated generation of EEG reports.